Patients with Schizophrenia and Self-Care - Arsova, Slavica; Bajraktarov, Stojan; Barbov, Ivan; Hadzihamza, Kadri (Scientific Foundation SPIROSKI, 2014)
INTRODUCTION: Patients with schizophrenia have severe problems with self-care which affects their quality of life.OBJECTIVE: The aim of the paper was to monitor self-care in patients with schizophrenia and to find out the differences regarding socio-demographic characteristics and ambulatory and day hospital treatment.METHOD: The investigation included 120 subjects each with diagnosis F20 according to ICD 10 criteria; divided in two groups of 60 patients regarding their actual treatment (the first group received ambulatory care whereas those from the second group had a day hospital treatment). Patients were of different age and gender, receiving regular antipsychotic therapy. They were included in individual and group psychosocial therapeutic procedures during the day hospital treatment. The investigation utilized the following diagnostic instruments: standardized clinical interview and Personal and social performance scale (PSP scale), non-standardized questionnaire of socio-demographic data, family support and existence of mental disorder in other family members.RESULTS: The results have shown better personal and social functioning in patients who had family support, in those who are employed, in those with no mental disorder in other family members and in patients on day hospital treatment against patients receiving ambulatory care.CONCLUSION: Day hospital treatment, family support and social support improve self-care of patients with schizophrenia.